Clinical and Laboratory Predictors of Deep Vein Thrombosis in Ovarian Malignant Tumor - Kusuma, Fitriyadi; Sitorus, Christina (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To investigate the clinical and laboratory predictors of symptomatic deep vein thrombosis (DVT) in ovarian malignant tumor. Methods: One hundred sixteen patients with suspected ovarian malignant tumor were recruited. Age, body mass index (BMI); D-dimer, fibrinogen, thrombocyte level, comorbid, tumor diameter, staging, distant metastasis, ascites, histopathology, length of surgery, blood loss and transfusion were recorded. Results: Incidence of symptomatic DVT was 16.5% and 88.2% cases occurred before surgery. No case of symptomatic DVT during postoperative care was found. Predictors of DVT were distant metastasis (OR 28.99; 95% CI 3.83-219.52, BMI ≥ 22.7 kg/m2 (OR 15.52, 95% CI 2.24-107.37), D-Dimer ≥ 1700 mg/ml (OR 13.30, 95% CI 2.40- 73.84), advanced stage (OR 6.66; 95% CI 1.05-42.27), epithelial tumor (OR 6.5; 95% CI 0.34-125.75), tumor’s diameter ≥ 18.25 cm (OR 2.36, 95% CI 0.48-11.54), and comorbidity (OR 2.49, 95% CI 0.53-11.66). Prediction score of DVT were score 3 for distant metastasis, BMI ≥ 22.7 kg/m2, D-Dimer ≥ 1700 mg/ml, score 2 for advanced stage, score 1 for tumor diameter ≥ 18.25 cm, comorbid, epithelial tumor and score 0 for the absence of variables or its value less than the cut off. Total score ≥ 8 of 14 is the least score which has a good predictive value for DVT with AUC 0.92, 95% CI 0.86-0.92, probability 86.46%. Conclusion: Distant metastasis and D-dimer are independently associated with the development of DVT in ovarian malignant tumor. [Indones J Obstet Gynecol 2017; 5-3: 180-184] Keywords: deep vein thrombosis, D-dimer, ovarian malignant, tumor predictor